2020
DOI: 10.3389/fneur.2020.00889
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Prediction in Ischemic Stroke: A Comparison of Machine Learning Algorithms and Regression Models

Abstract: Background and Purpose: Stroke-related functional risk scores are used to predict patients' functional outcomes following a stroke event. We evaluate the predictive accuracy of machine-learning algorithms for predicting functional outcomes in acute ischemic stroke patients after endovascular treatment. Methods: Data were from the Precise and Rapid Assessment of Collaterals with Multi-phase CT Angiography (PROVE-IT), an observational study of 614 ischemic stroke patients. Regression and machine learning models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…ML techniques presented over 0.94 AUC in both ischemic and hemorrhagic stroke using preadmission and inpatient data 27 . Alaka et al concluded that both logistic regression and ML models had comparable predictive accuracy at 90 days when validated internally (AUC range = [0.65–0.72]) and externally (AUC range = [0.66–0.71]) in acute IS patients after endovascular treatment (n = 614–684) 28 .…”
Section: Discussionmentioning
confidence: 99%
“…ML techniques presented over 0.94 AUC in both ischemic and hemorrhagic stroke using preadmission and inpatient data 27 . Alaka et al concluded that both logistic regression and ML models had comparable predictive accuracy at 90 days when validated internally (AUC range = [0.65–0.72]) and externally (AUC range = [0.66–0.71]) in acute IS patients after endovascular treatment (n = 614–684) 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous published articles [53][54][55] merely compared the difference in predictive accuracy with AUC among ML methods. However, none demonstrated a real app that can be a useful, feasible, e cient, and effective device applied to clinical settings, as we did providing a prototype with an ML method in a study for readers to manipulate it on their own on dashboards as we did in Figures 4 and 5.…”
Section: The Strength and Features In This Studymentioning
confidence: 99%
“…Furthermore, numerous published articles [53][54][55] merely compared the difference in predictive accuracy with AUC among ML methods. However, none demonstrated a real app that can be a useful, feasible, e cient, and effective device applied to clinical settings, as we did providing a prototype with an ML method in a study for readers to manipulate it on their own on dashboards as we did in Figs.…”
Section: The Strength and Features In This Studymentioning
confidence: 99%